Tunisia's Experience with Real Exchange Rate Targeting and the Transition to a Flexible Exchange Rate Regime. (IMF Working Papers; Working Paper, 2002)
Over the past decade or so, Tunisia has experienced a strong economic performance while pursuing a constant real exchange rate rule (CRERR). The limitations of this rule are now beginning to emerge in the context of a more open economy, regional integration, a more market-based monetary policy, and the desire to relax capital controls. This paper explores how Tunisia avoided the pitfalls of real exchange rate targeting as predicted by the theoretical models. By estimating the equilibrium real exchange rate based on fundamental variables and assessing different measures of competitiveness, the paper finds no evidence of a misalignment in the current level of the exchange rate.